Team Performance in Dynamic Settings: Evaluating Shared Team Mental Model Similarity & Accuracy (Journal of Organizational Psychology, 2020)
Teamwork in dynamic conditions relies on accurate/similar shared task mental models. Consensus exists in extant literature that shared task mental model (STMM) accuracy, rather than STMM similarity is important for team performance. This study examines the conceptual and measurement issues underlying these earlier findings and tested the complementary role of both STMM accuracy and similarity to team performance in a real world simulation of dynamic teamwork among forty-four (44) 3-member teams. The discussion focused on the implications of these findings firstly to the measurement of shared task mental models, and to future conceptualization of shared task mental models.
Keywords: Organizational Psychology; shared team mental model; paired ratings; team performance; Accuracy